The Digital Scalpel: Comparing AI Surgical Planning and the Surgeon's Traditional Approach - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The Digital Scalpel: Comparing AI Surgical Planning and the Surgeon's Traditional Approach The operating room is a domain of precision, experience, and ...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Machine Learning; Medical Ethics